2001
DOI: 10.1081/ncn-100002531
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitized and Catalytic Oxidation of Dna by Metallophthalocyanine-Oligonucleotide Conjugates

Abstract: The synthesis of new metallophthalocyanine-oligonucleotide conjugates is reported. These conjugates can cause sequence-specific photosensitized or catalytic oxidation of DNA by molecular oxygen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…The labelled oligonucleotides were prepared using a previously reported method (14). The oligonucleotides were synthesized by standard phosphoramidite chemistry and contained a—O-(CH 2 ) 3 NH 2 linker at the 5′-end.…”
Section: Methodsmentioning
confidence: 99%
“…The labelled oligonucleotides were prepared using a previously reported method (14). The oligonucleotides were synthesized by standard phosphoramidite chemistry and contained a—O-(CH 2 ) 3 NH 2 linker at the 5′-end.…”
Section: Methodsmentioning
confidence: 99%
“…The oligonucleotide conjugates with phthalocyanine complexes of Al(III), Zn(II), and Co(II) were synthesized using a previously reported solid-phase method [13] with a 30–40% yield. The conjugates were isolated from the reaction mixture and purified by HPLC in an acetonitrile/water gradient.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Koval et al have first reported in 2001 the synthesis of oligonucleotide-phthalocyanines conjugates for specific DNA modifications in vitro and in vivo, which is of interest for the development of sequence specific gene targeting reagents [92]. Later on, Hammer et al prepared asymmetrical water-soluble Pcs 19-20 conjugated with an oligonucleotide via an isothiocyanate function (Fig.…”
Section: Biotinementioning
confidence: 98%